Differential expression of transforming growth factors alpha and beta in rat intestinal epithelial cells. - Koyama, S Y (1989)
Expression of transforming growth factor alpha (TGF alpha), and transforming growth factor beta (TGF beta) was assessed in isolated primary rat intestinal epithelial cells as well as a rat intestinal crypt cell-derived cell line (IEC-6). A gradient in TGF beta was present, with high concentrations of a 2.5-kb transcript found in undifferentiated crypt cells and progressively lower amounts of the TGF beta transcript in increasingly differentiated villus cell populations. In contrast, the concentration of 4.5-kb TGF alpha transcript was higher in differentiated villus cells than in mitotically active, undifferentiated populations of crypt epithelial cells. The concentrations of transforming growth factors alpha and beta as determined by radioreceptor binding inhibition assay and direct assessment of transforming growth factor biological activity correlated with Northern blot analysis. Although gradients in the expression of the TGFs were present, equivalent binding was observed in the different intestinal cell populations when assessed with 125I-TGF beta and 125I-EGF (TGF alpha). No EGF transcripts were detected in any intestinal cell population, suggesting that the true ligand of the EGF receptor was TGF alpha. IEC-6 cells expressed both TGF alpha and TGF beta transcripts. In addition to the transcripts identified in the primary intestinal cells, this cell line contained an additional larger TGF alpha transcript (4.8 kb) and smaller TGF beta transcripts (2.2 and 1.8 kb). TGF alpha and TGF beta may play a significant role in the regulation of the balance between proliferative and differentiated cell compartments in the intestinal epithelium through both autocrine and paracrine mechanisms.